Carved in stone - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Blackstone legacy, 2021)
"When lawyer Patrick O'Neill agrees to resurrect an old mystery and challenge the Blackstones' legacy of greed and corruption, he doesn't expect to be derailed by the kindhearted family heiress, Gwen Kellerman. She is tasked with getting him to drop the case, but when the mystery takes a shocking twist, he is the only one who can save her from danger"--